“It Is Not Their Fault”. Discourses on Immigration after the Irruption of the Radical Right in the Spanish Political System - Mariscal-de-Gante, Álvaro; Rinken, Sebastian (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
Due to the irrelevance of nativist parties and the predominance of tolerant migration attitudes, Spain used to be considered an exception among European countries. The irruption of the radical right party VOX into the political system constitutes a sea change at this regard: the institutional presence of xenophobic discourse may affect the evolution of attitudes toward immigration and immigrants. Based on focus groups conducted shortly after VOX’ first electoral success, this study examines the inclination of Spanish citizens to blame immigrants for various kinds of economic difficulties. Our findings suggest that the collective experience of the Great Recession shields Spain’s immigrant population to quite some extent against the role of the culprit. The “VOX effect” on immigration attitudes turns out to be surprisingly varied, since it comprises a revitalization of universalist conceptions.
Keywords: Attitudes toward immigration and immigrants; xenophobia; radical right party; political polarization; Spain